Non-fungible tokenin (NFT:n) mahdollisuudet syrjäyttää keräilykortit – Laadullinen haastattelututkimus - Ylönen, Riku (2025)
In recent years, Non-Fungible Tokens (NFTs) have emerged as a modern form of collectibles. The term NFT can be translated into Finnish as "ei-vaihtokelpoinen rahake", and collectible NFTs can consist of movies, images, games, or iconic moments in sports. NFT is based on blockchain technology. It makes easier to collect digital moments compared to physical trading cards.